Udep Saree and Matee syahid: Local Ethical Reasoning in Acehnese Anti-Colonial Resistance - Muhammad Maulana; Iskandar; Muhammad Hendri; Gustira Monita (Center for Research and Development of Religious Literature and Heritage, 2026)
This article examines udep saree, matee syahid; an Acehnese hadih maja expression translated here as